2013
DOI: 10.1038/hdy.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution and the latitudinal biodiversity gradient

Abstract: Species density is higher in the tropics (low latitude) than in temperate regions (high latitude) resulting in a latitudinal biodiversity gradient (LBG). The LBG must be generated by differential rates of speciation and/or extinction and/or immigration among regions, but the role of each of these processes is still unclear. Recent studies examining differences in rates of molecular evolution have inferred a direct link between rate of molecular evolution and rate of speciation, and postulated these as importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 134 publications
(203 reference statements)
4
83
1
Order By: Relevance
“…Firstly, the pattern of a latitudinal biodiversity gradient was evaluated, that is, whether species richness or diversity increases towards lower latitudes [38, 39]. The latitudinal gradient of alpha diversity was analyzed by a linear regression.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the pattern of a latitudinal biodiversity gradient was evaluated, that is, whether species richness or diversity increases towards lower latitudes [38, 39]. The latitudinal gradient of alpha diversity was analyzed by a linear regression.…”
Section: Resultsmentioning
confidence: 99%
“…However, our data provide no support for this hypothesis and indeed suggest the opposite pattern: average UV exposure is negatively correlated with organelle mutation rate. The role of UV as a determinant of substitution rate is also undermined by patterns of variation in rate of molecular evolution with altitude (Dowle et al 2013). UV exposure increases with altitude, yet several studies have shown that rates of molecular evolution decrease with altitude (Gillman et al 2009;Wright et al 2010).…”
Section: Environmental Effects On Molecular Evolutionmentioning
confidence: 99%
“…A second general hypothesis suggests that metabolic rate influence the pace of evolution in acting on mutation rate [1], [2], [3], [8], [12]. In particular, higher metabolic activity is associated with higher oxygen consumption and release of free radicals, which may in turn induce higher mutation rates and rapid genetic divergence.…”
Section: Introductionmentioning
confidence: 99%